2018
DOI: 10.1186/s13014-018-1107-x
|View full text |Cite
|
Sign up to set email alerts
|

International validation of the EORTC QLQ-PRT20 module for assessment of quality of life symptoms relating to radiation proctitis: a phase IV study

Abstract: BackgroundAlthough patients experience radiation proctitis post radiotherapy no internationally tested instruments exist to measure these symptoms. This Phase IV study tested the scale structure, reliability and validity and cross-cultural applicability of the EORTC proctitis module (QLQ-PRT23) in patients who were receiving pelvic radiotherapy.MethodsPatients (n = 358) from six countries completed the EORTC QLQ-C30, QLQ-PRT23 and EORTC Quality of Life Group debriefing questions. Clinicians completed the EORTC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…All patients were seen weekly after Week four, and patient toxicity was recorded on a weekly basis. Each patient completed the International Prostate Symptom Score (IPSS) questionnaire, 17 EORTC Quality of Life Questionnaire Prostate Cancer Module (EORTC QLQ PR25) and EORTC QLQ C30 Quality of Life Questionnaire 18,19 at the time of the planning CT and then weekly after the fourth week until completion of treatment.…”
Section: Methodsmentioning
confidence: 99%
“…All patients were seen weekly after Week four, and patient toxicity was recorded on a weekly basis. Each patient completed the International Prostate Symptom Score (IPSS) questionnaire, 17 EORTC Quality of Life Questionnaire Prostate Cancer Module (EORTC QLQ PR25) and EORTC QLQ C30 Quality of Life Questionnaire 18,19 at the time of the planning CT and then weekly after the fourth week until completion of treatment.…”
Section: Methodsmentioning
confidence: 99%
“…A review by Atkinson et al investigating the association between CTCAE and PRO found poor agreement between well-validated PRO measures and clinician rating (CTCAE) for proctitis among patients with rectal or anal cancer [ 52 ]. A few years later, EORTC validated the first radiation proctitis-specific quality-of-life module (QLQ-PRT20) [ 53 ]. It comprises 21 items, some of which (i.e., rectal pain, diarrhea and rectal bleeding) were already included in the pelvic item set.…”
Section: Discussionmentioning
confidence: 99%
“…EORTC QLQ-PRT20 questionnaire, unlike the speci c pathology modules of the EORTC, is focused on QoL related to side effects and is effective in detecting intestinal symptoms related to radiotherapy. In addition, it is able to identify changes in the symptoms of patients, proving to be adequate in the evaluation of acute changes after pelvic radiotherapy (9). This study was able to detect worsening of symptoms of fecal urgency and leakage, data that are usually underestimated in the assessment of quality of life.…”
Section: (15)mentioning
confidence: 88%
“…The relevence of patient reported outcomes (PROs) has increased in decision-making and, therefore, efforts have been made to standardize these data (7). The European Organisation of Research and Treatment of Cancer (EORTC) Quality of Life Group (QLG) developed the EORTC QLQ-PRT20, a module for RP that could be applied with the core QoL questionnaire EORTC QLQ-C30 (5,(8)(9)(10). The questionnaire's validation was published in 2018 by Halkett et al and it focuses on QoL related to RP, evaluating bowel symptoms that patients may experience during or after pelvic radiotherapy (9).…”
Section: Introductionmentioning
confidence: 99%